Hydroelastic Behavior of a Floating Membrane Breakwater in Shallow Water - Panduranga, Kottala; Koley, Santanu (Discontinuity, Nonlinearity, and Complexity, 2026)
This work presents an analytical approach to analyze the hydroelastic behavior of floating membrane breakwater under the assumption of linear shallow water theory. The analysis is carried out by assuming that the membrane bottom surface is at the water's surface and the transverse vibration of the membrane is seen as a wave propagating over the membrane breakwater. The solution to the associated problem is obtained by matching the wave propagation in the membrane to the wave propagation at the bottom of the membrane surface. It is seen that the amplitude of the deflection of the membrane decreases with an increase in the tensile force.